Main Inverse Problem for Differential Systems With Degenerate Diffusion - Ibraeva, G. T.; Tleubergenov, M. I. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
The separation method is used obtain sufficient conditions for the solvability of the main (according to Galiullin’s classification) inverse problem in the class of first-order Itô stochastic differential systems with random perturbations from the class of Wiener processes and diffusion degenerate with respect to a part of variables.